PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN GARUDA INDONESIA DI DENPASAR - Wendha, AA Ayu Atika Paramitha; Rahyuda, I Ketut; Suasana, I Gst Agung Ketut Gede (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2013)
The aim of this research is to know the effect of service quality on satisfaction and loyalty on Garuda Indonesia passengers in Denpasar. Respondent of this research at least 17 years old who use the services of Garuda Indonesia at least three times in this year. The number of respondents on this research defined 180 respondents by using sampling technique that is purposive sampling. This research used analysis od Structural Equation Modeling (SEM) with the help of AMOS program. The result of this research showed that the hypothesisare supported : 1) service quality has positive and significant impact on satisfaction, 2) satisfaction has positive and significant impact on loyalty, 3) service quality has positive and significant impact on loyaltyof Garuda Indonesia in Denpasar.
Keywords: service quality; customer satisfaction; customer loyality